2011
DOI: 10.3136/fstr.17.437
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Extraction Process of Crude Protein from Grape Seeds by RSM

Abstract: Grape seed is a potential source of edible protein, so effective extraction of protein component from grape seed seems to be very important. However, so far, such information is unavailable. In this study, the conditions for protein extraction from the grape seeds were optimized by the single factor test and the response surface methodology (RSM). A box-behnken design (BBD) was used for experimental design and analysis of the results to obtain the optimal extraction conditions. Solvent/meal ratio, extraction t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 30 publications
2
13
1
Order By: Relevance
“…Hence, 1:20 (solid to alkali ratio) was selected as optimal to increase protein content in extraction. A similar solid/solvent ratio was obtained by Lv et al (2011), during grape seeds protein extraction.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…Hence, 1:20 (solid to alkali ratio) was selected as optimal to increase protein content in extraction. A similar solid/solvent ratio was obtained by Lv et al (2011), during grape seeds protein extraction.…”
Section: Resultssupporting
confidence: 62%
“…Hence, 40°C was considered as an optimum temperature in the experiment. A similar kind of study was performed for grape seed protein (Lv et al 2011). Deng et al (2014) also observed a decrease in protein content of kiwifruit seeds with increased temperature (above 35°C) due to the denaturation of proteins.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Earlier studies had reported that the solvent concentration is the most important factor in the extraction of different components from plant material (Liyana‐Pathirana and Shahidi ; Lv et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…Various methods of protein extraction have been reported for different protein sources including grape seeds (Lv et al . ), pumpkin seeds (Li and Fu ), eggs (Lin et al . ), milk and muscle proteins (Liu et al .…”
Section: Introductionmentioning
confidence: 99%